Protecting Human Rights in the Pacific - Butler, Petra (Victoria University of Wellington Law Review, 2009)
Between 27 and 29 April 2008, the International Centre for the Legal Protection of Human Rights hosted a human rights law conference. This introductory article provides an overview of the papers presented on the 28th and 29th. The idea for the conference emerged when a break-out group from another conference discussed whether the 1989 LAWASIA Pacific Human Rights Charter could be revived. The aim of this conference was to identify key human rights challenges in the Pacific and strategies for strengthening national, regional and international mechanisms for enhanced protection of human rights in the region. Representatives were asked to prepare country reports on their respective states having regard to the following human rights issues: health, environment, culture and language, education, and the rule of law.